Emerging strategies of activatable MR imaging probes and their advantages for biomedical applications. Issue 5 (21st May 2021) - Jin, Xiao; Yang, Weitao; Xu, Yan; Bian, Kexin; Zhang, Bingbo
Abstract: Magnetic resonance imaging (MRI) is a highly valuable diagnostic tool as it is a noninvasive technique that offers high spatial resolution. The use of contrast agents (CAs) can enhance the precision and specificity of MRI for disease diagnosis, but their imaging signals are "always on" regardless of whether they interact with target tissues or cells. Hence, a poor target‐to‐background signal ratio (TBR) is inevitably produced. In contrast, activatable CAs with high performance have been used to significantly improve the TBR, thus these CAs have also received extensive attention and undergone in‐depth research. In this review, we summarized the recent advances in design strategies and principles of activatable MR CAs, including ion conversion, self‐assembly, and disassembly. Additionally, we analyzed the advantages of these strategies in biomedical applications from in vitro biodetection to in vivo disease diagnosis compared to the outcomes of conventional MR CAs. Finally, we discussed the potential limitations, proposed solutions, and future perspectives of these activatable CAs. Abstract : A comprehensive review is presented on the recent progress of three design strategies (ion extraction, self‐assembly, and disassembly) of activatable MRI probes and highlights their advantages in biomedical applications, including, in vitro biodetection, in vivo imaging and monitoring drug release. It is believed that low‐background imaging techniques are the development trend of MR imaging in the future and the study of activatable MRI probes is one of the key points in this field.